Attitude, Repurchase Intention, and Brand Loyalty toward Local Cosmetic Brands in Indonesia: A Conceptual Framework - Pramuditha, Salsabillah Putri Rizky Amanda; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (Formosa Journal of Multidisciplinary Research, 2025)
This study explores the relationship between attitude, repurchase intention, and brand loyalty towards local cosmetic brands in Indonesia. The cosmetic industry in Indonesia is rapidly evolving, with a growing number of local brands competing for consumer attention. Key factors influencing consumer behavior include brand image, trust, perceived value, and satisfaction. This research employs a quantitative approach, utilizing surveys to gather data from consumers who have previously purchased local cosmetic products. The findings indicate that positive consumer attitudes significantly enhance repurchase intentions, which in turn foster brand loyalty. Moreover, brand trust and perceived value are critical determinants of repurchase intention, while brand image has a less pronounced effect. These insights provide a conceptual framework for understanding consumer behavior in the local cosmetic market and highlight the importance of fostering positive brand relationships to enhance loyalty and repeat purchases.